2003
DOI: 10.1097/00008571-200301000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Natural allelic variants of breast cancer resistance protein (BCRP) and their relationship to BCRP expression in human intestine

Abstract: The aim of this study was to identify the extent of genetic variability in breast cancer resistance protein (BCRP) in humans. We first analysed the sequence of BCRP cDNA from human livers and from human intestines phenotyped for expression of intestinal BCRP. We then determined the frequency of all known coding single nucleotide polymorphisms (cSNPs) using DNA from individuals representing 11 different ethnic populations. Nine SNPs including four non-synonymous and three synonymous cSNPs and two intronic SNPs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
196
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(212 citation statements)
references
References 16 publications
15
196
0
1
Order By: Relevance
“…Allelic variation as a result of SNPs results in alterations of the BCRP protein at amino acids 12 (V12M), 141 (Q141K), 206 (I206L), and 590 (N590Y), with the most frequent polymorphisms being the exon 2 SNP (G34A) and the exon 5 SNP (C421A), which produce changes in amino acids 12 and 141 (Honjo et al, 2002;Imai et al, 2002a;Zamber et al, 2003). Additionally, a splice variant was found that resulted in deletions of A315 and T316 (Imai et al, 2002a).…”
Section: Normal Allelic Variants Of Bcrpmentioning
confidence: 99%
“…Allelic variation as a result of SNPs results in alterations of the BCRP protein at amino acids 12 (V12M), 141 (Q141K), 206 (I206L), and 590 (N590Y), with the most frequent polymorphisms being the exon 2 SNP (G34A) and the exon 5 SNP (C421A), which produce changes in amino acids 12 and 141 (Honjo et al, 2002;Imai et al, 2002a;Zamber et al, 2003). Additionally, a splice variant was found that resulted in deletions of A315 and T316 (Imai et al, 2002a).…”
Section: Normal Allelic Variants Of Bcrpmentioning
confidence: 99%
“…[12][13][14] BCRP also belongs to the ABC efflux transporter superfamily 26 and is widely expressed in the small intestine, liver and placenta, influencing the absorption and disposition of a variety of substrates. 27,28 It is noteworthy that Petain et al reported that IM clearance in patients carrying the ABCG2 421C/A genotype was significantly lower than in those with the 421C/C genotype.…”
Section: Introductionmentioning
confidence: 99%
“…previously published for Caucasians by other groups. 14,23,29 For all 6 SNPs investigated, there are no significant differences in the allele frequencies when comparing SCLC with NSCLC patients.…”
Section: Patient Characteristics and Treatment Information Are Given Inmentioning
confidence: 87%
“…23 A second polymorphism, ABCG2 G34A, has also been described. In cell line experiments Mizuarai et al 24 found the 34A-Allele leading to disturbed localization in the plasma membrane and decreased drug efflux, whereas Yanase et al 18 reported the drug resistance profile of the 34A variant to be similar to the wildtype.…”
mentioning
confidence: 99%